Percussion Drilling of Deep Holes Using Picosecond Ultrashort Pulse Laser in Ni-Based Superalloy Coated with Ceramic Thermal Barrier Coatings - Liu, Haodong (Materials (Basel), 2020)
Ni-based superalloy with ceramic thermal barrier coatings (TBCs) is a composite material, which can be used in special environments with high temperature and high pressure such as aeroengine blade. In order to improve the cooling effect of the aeroengine, it is necessary to perform multi-size and large-area holes processing on the surface of blades. As a non-contact processing method with fast processing speed, good processing quality and almost no deformation, laser processing has been one of the important processing methods for film cooling hole processing of aeroengine blades. Percussion drilling is presented using picosecond ultrashort pulse laser in order to explore processing of deep holes in Ni-based superalloy, ceramic TBCs, and ceramic TBCs/substrate multilayer material. The effects of pulses, threshold and wavelength on hole diameter have been discussed, and the experiment on the deep hole ablation with 1064 nm wavelength has been performed. By analyzing the hole size and morphological characteristics of multiple processing parameters, the variation of hole cylindricity is obtained. A high-quality hole, without spatters around the periphery of hole entrance and without recast layer on the side-wall surface, in Ni-based superalloy coated with ceramic TBCs has been drilled. This research has potential applications to blade film cooling holes.